2015
DOI: 10.1186/s40064-015-1268-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of nosocomial Clostridium difficile infection in pediatric ward in Iran

Abstract: Clostridium difficile is recognized as a major cause of nosocomial acquired antibiotic-associated diarrhea and pseudomembranous colitis. It is a significant financial burden on modern healthcare resources. This study aimed to assess the molecular characterization of C. difficile strains isolated from children under 5 years old suffered from nosocomial diarrhea. One hundred diarrheic and 130 non-diarrheic fecal samples were collected from pediatrics less than 5 years old. Samples were cultured and C. difficile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
0
22
2
Order By: Relevance
“…In our study the prevalence of CDI and the distribution of the causative RTs differed greatly between hospitals in various districts of Tehran. Compared to previous data from Iran, a noticeable heterogeneity was observed among published studies particularly in terms of the study population and the prevalence of CDI that varied from 6.14% to 52% [20][21][22][31][32][33][34]. Compared to other countries, the prevalence of CDI in our study (15.9%) was lower than that reported in Europe, America and the Middle East [28,[35][36][37].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In our study the prevalence of CDI and the distribution of the causative RTs differed greatly between hospitals in various districts of Tehran. Compared to previous data from Iran, a noticeable heterogeneity was observed among published studies particularly in terms of the study population and the prevalence of CDI that varied from 6.14% to 52% [20][21][22][31][32][33][34]. Compared to other countries, the prevalence of CDI in our study (15.9%) was lower than that reported in Europe, America and the Middle East [28,[35][36][37].…”
Section: Discussioncontrasting
confidence: 92%
“…In order to monitor the emergence of new RTs or identify a common RT cluster in a suspected CDI outbreak, effective CDI surveillance requires the collection of epidemiological data that includes the characterization of causative C. difficile strains and a capillary gel-based electrophoresis (CE-ribotyping), which is the recommended typing method [18,19]. Information on the molecular epidemiology of CDI in Iran, especially with a longitudinal perspective, is limited [20][21][22]. Therefore, in order to obtain data on CDI epidemiology and distribution of C. difficile RTs in Tehran healthcare settings, and to identify the risk factors for CDI development in Iranian population, we performed a 14-year-long cross-sectional study on patients with diarrhea between December 2004 and November 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Studies which have been done in this field in Iran are scarce. Khoshdel et al (2015) (23) revealed that 52% of diarrheic and non-diarrheic stool samples of Iranian children were positive for C. difficile which was entirely higher than our results. They showed that boys and 13 to 24-month age children had the higher prevalence of C. difficile .…”
Section: Discussioncontrasting
confidence: 86%
“…A recent study conducted on 400 pediatric stool specimens in Iran reported a high prevalence for R27 (14.28%), R1 (10.71%), R12 (7.14%), R13 (7.14%), and R18 (7.14%) (21). In another study in Iran, Khoshdel et al (2015) (22) reported that the most commonly detected RTs in the C. difficile isolates of pediatrics were RT027 (11.52%), RT01 (9.61%), and RT013 (7.68%). In a teaching hospital-based study (23) (between 2010 and 2011), 11 different ribotyping patterns were identified (IR1-10, 078, 014), and RT078 was the most common (21%).…”
Section: Discussionmentioning
confidence: 93%
“…isolates. The incidence of tcdA À /tcdB + C. difficile strains is extensively increasing and ranges from 3% to 92% worldwide (22). In China, Huang et al reported that 33.3% of 75 toxigenic isolates were tcdA À /tcdB + (32).…”
Section: Discussionmentioning
confidence: 99%